ALTERNATIVE ENERGY IN UKRAINE: STATE AND PROSPECTS OF DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
This article assesses the current state of alternative energy in Ukraine and the world, as well as assesses the experience of other countries in the development of "clean" energy. Due to the constant growth of energy consumption, the question arises of the development of alternative renewable energy sources with minimal impact on the environment. As this issue is raised and studied in many countries for a long time, our country can compare foreign experience in this area and use methods to stimulate the development of alternative energy. Which proved to be the best. In Ukraine, the "green tariff" has been in force for a long time, the size of which is gradually decreasing, but in other countries, other methods of incentives have been positively recommended.. As a result of the work, the main directions of alternative energy were considered. It has been established that one of the best methods of stimulating the development of "clean" energy is the use of "green tariffs" and support through grants. Ukraine has quite progressive legislation in the field of green tariffs, but in our opinion this is not enough. The introduction of partial compensation for the cost of power plants from alternative energy sources can significantly accelerate the development of this industry. In addition, non-financial incentives, such as social advertising, should be used. When stimulating the development of "clean" energy, it is also necessary to take into account its negative impact on the environment and take measures to minimize it. When implementing alternative energy, it should be borne in mind that it can also harm the environment if used incorrectly. The negative impact of alternative energy can be reduced by using standardized norms, which define restrictions on the use of certain types of alternative energy under certain conditions.
Keywords: renewable energy sources, alternative energy